2012
DOI: 10.1001/archopthalmol.2011.1224
|View full text |Cite
|
Sign up to set email alerts
|

Projected Clinical Outcomes of Glaucoma Screening in African American Individuals

Abstract: Routine glaucoma screening for middle-aged African American individuals is potentially clinically effective but its impact on visual impairment and blindness may be modest. However, we did not assess the impact on visual field loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
(49 reference statements)
0
17
0
8
Order By: Relevance
“…For example, Ladapo and colleagues estimated that implementation of a national glaucoma screening program for African Americans aged 50 to 59 years with unrecognized glaucoma would reduce the lifetime prevalence of undiagnosed glaucoma from 50% to 27%. 30 …”
Section: Discussionmentioning
confidence: 99%
“…For example, Ladapo and colleagues estimated that implementation of a national glaucoma screening program for African Americans aged 50 to 59 years with unrecognized glaucoma would reduce the lifetime prevalence of undiagnosed glaucoma from 50% to 27%. 30 …”
Section: Discussionmentioning
confidence: 99%
“…The combination of higher lifetime risks and lower medical support place a double burden on this group. Previous studies have suggested that nationwide implementation of screening middle aged African Americans could decrease the rate of undiagnosed glaucoma from 50% to 27%(25). Earlier screening and diagnosis enables patients to more effectively leverage current treatment options to reduce the risk of bilateral blindness later in life(25).…”
Section: Genetic Epidemiology Of Poagmentioning
confidence: 99%
“…A well-known barrier for individuals seeking medical attention is low socioeconomic status which disproportionally affects African Americans[32]. Additionally, at least one study suggests that the lifetime prevalence of undiagnosed glaucoma in African Americans is 50%[33]. This may in part explain the limited number of African American POAG cases (n = 267) representing only 2.82% of African Americans in EAGLE BioVU.…”
Section: Discussionmentioning
confidence: 99%